2022
DOI: 10.1155/2022/9084852
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Comparison between cTACE and H101-TACE in Unresectable Hepatocellular Carcinoma (HCC): A Propensity-Score Matching Analysis

Abstract: Background. Transarterial chemoembolization (TACE) is the most common treatment for patients with HCC who are unsuitable for radical therapies. Conventional TACE (cTACE) takes advantage of the preferential hepatic arterial supply of HCC for the targeted delivery of chemotherapeutic agents suspended in lipiodol, followed by embolization or reduction of arterial flow using various types of particles while sparing the surrounding liver parenchyma. Aims and Objectives. The current study is aimed at comparing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Recent articles compare the efficacy and safety characteristics of recombinant human type 5 adenovirus transarterial infusion (H101-TACE) and conventional transarterial chemoembolization (cTACE) in patients with unresectable hepatocellular carcinoma (HCC). A meta-analysis done on the combination of tyrosine kinases and TACE shows promising results for the combination therapy [ 20 , 21 ]. Camrelizumab targets the programmed cell death protein PD-1 and prevents its interactions with its ligands, blocking the antitumor immune response, and resulting in antitumor effects [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recent articles compare the efficacy and safety characteristics of recombinant human type 5 adenovirus transarterial infusion (H101-TACE) and conventional transarterial chemoembolization (cTACE) in patients with unresectable hepatocellular carcinoma (HCC). A meta-analysis done on the combination of tyrosine kinases and TACE shows promising results for the combination therapy [ 20 , 21 ]. Camrelizumab targets the programmed cell death protein PD-1 and prevents its interactions with its ligands, blocking the antitumor immune response, and resulting in antitumor effects [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“… 12 , 13 Additionally, to enhance safety, a portion of its E3 region has also been deleted. 14 It has been shown to enhance transarterial chemoembolization (TACE) for HCC 15 , 16 , 17 and conventional chemotherapy for other tumors. 18 , 19 , 20 Approved in China for advanced nasopharyngeal carcinoma since 2005, H101 represents the first OV to gain regulatory approval.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%